Political propaganda in the British media of the late 1930s (using the example of the humanitarian aspect of the Spanish Civil war 1936–1939) - Malay, Vera V.; Fomichev, Nikolay N. (Journal of the Belarusian State University. International Relations, 2018)
The article deals with problems of information warfare history using the example of the British media of the 1930s. The British printed propaganda of the second half of the 1930s presents the object of the study. Its political aspect using the example of humanitarian issues coverage during the Civil War in Spain 1936 –1939 is the subject of research. The purpose of research is to give characteristics to interpretations of humanitarian aspects of the Spanish conflict 1936–1939 by the British printed propaganda. It is based on the principles of historicism (understanding of historical facts and phenomena in their interconnection and development in time) and objectivity. Based on the study of about 20 editions of the British press of va rious political directions, the authors come to the conclusion that a humanitarian disaster as a result of the Spanish War 1936–1939 was recognized by all the editions, however, it was interpreted according to their political preferences. The humanitarian content of the Spanish events provoked sharp polarization of the public opinion in the UK. Major newsbreaks were the following: sufferings of the civil population; refugee problem and the public reaction in Britain towards it; humanitarian campaigns. A “moral standard” of criticism towards the “enemy” was boldly outlined – the focus was made on the inhumanity and threat emanating from him. The Spanish problematic was actively used in information and psychological confrontation and the formation of the “image of the enemy” on the eve of the Second World War.
Keywords: British printed propaganda; image of the enemy; information warfare; humanitarian aspects; Spanish Civil War of 1936–1939